Corporate Pathways to Sustainability through Resource Management in Indian Enterprises - Rayaprolu Viswaprasad; K. Sunitha; S. Dhanya Sri; Neeraja. S. Parvataneni (PT Agung Media Publisher, 2025)
India’s private sector plays a pivotal role in achieving national and global sustainability goals amid rapid economic growth and environmental challenges. This study employed a qualitative-comparative approach by analyzing sustainability practices of five leading conglomerates namely Tata Group, Aditya Birla Group, Reliance Industries, Adani Group, and ITC using company reports, secondary data, and sectoral benchmarks. Three thematic areas were examined: (1) water and energy management, (2) material management and circular economy, and (3) corporate sustainability goals. The findings show measurable progress in resource efficiency: Tata Steel reduced water consumption by 24.5% (2012–2023), Tata Motors cut energy use per vehicle by 16.2% (2012–2023), and UltraTech Cement substituted 21% of virgin raw materials with industrial waste (target 50% by 2030). Renewable adoption reached 27.8% in Tata Group’s energy mix, while Reliance developed a 20 GW renewable portfolio. Strategic goals vary, with Adani committing to net-zero by 2029, Tata Group by 2045, and Reliance by 2070, reflecting different levels of ambition and feasibility. Indian conglomerates demonstrate alignment with international climate agendas through renewable investment, carbon reduction, and circular economy models. However, uneven disclosure, fragmented regulatory frameworks, and technological uncertainties remain challenges. Corporate sustainability in India has shifted from peripheral CSR activities to central business strategies, with resource management and net-zero commitments shaping competitiveness and resilience. Limitations include reliance on secondary data; future research should expand to primary fieldwork and cross-country comparisons to deepen insights into corporate sustainability pathways.